Superradiant black hole rocket - Acito, Lucas Agustín (2024)
We calculate the total thrust resulting from the interaction between charged scalar modes and a superradiant Reissner-Nordström black hole, when the modes are deflected by a hemispherical perfect mirror located at a finite distance from the black hole’s horizon.